2022
DOI: 10.1093/jas/skac043
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthetic oviductal fluid for Conventional Freezing 1 (SCF1) culture medium improves development and cryotolerance of in vitro produced Holstein embryos

Abstract: In vitro produced (IVP) embryos hold great promise in the cattle industry; however, suboptimal in vitro culture conditions induce metabolic dysfunction, resulting in poor development and low cryotolerance of IVP embryos. This limits the use of IVP embryos in the cattle industry for embryo transfer and commercial scale-up. Previous studies have reported the use of individual metabolic regulators in culture media to improve blastocyst development rates and cryopreservation. In this study, we hypothesized that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In addition, it did not quantify changes in embryos after treatment with sucrose medium. To overcome these limitations, further studies on conception rates in farmer’s fields by freeze-thawing bovine embryos pretreated with sucrose and direct embryo transfer are needed, and this study will help inform future frozen embryo transfer studies because embryo survival and conception rates are closely related ( 14 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it did not quantify changes in embryos after treatment with sucrose medium. To overcome these limitations, further studies on conception rates in farmer’s fields by freeze-thawing bovine embryos pretreated with sucrose and direct embryo transfer are needed, and this study will help inform future frozen embryo transfer studies because embryo survival and conception rates are closely related ( 14 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose is a non-penetrating cryoprotectant used for removing intracellular water and protecting cells from osmotic shock in freezing media ( 7 , 13 ). Bovine embryos were reportedly pre-equilibrated with sucrose before slow freezing; however, pretreatment did not improve embryo re-expansion and apoptosis rates ( 14 ). Bui-Xuan-Nguyen ( 15 ) pretreated bovine embryos with sucrose before slow freezing in a medium containing glycerol; however, viability did not improve.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hara [14] reported that the developmental ability of cryopreserved porcine oocytes could be improved by removing lipids after centrifugation. Despite the potential benefits, centrifugation and micromanipulation are considered too complex and timeconsuming for commercial use [15] and can negatively impact the subsequent development of oocytes [16], limiting their widespread application. As a result, researchers are focusing on using substances to enhance lipid metabolism, decrease lipid droplet content, and improve the cryopreservation outcome.…”
Section: Introductionmentioning
confidence: 99%